ECONOMIC SUSTAINABILITY OF AGRICULTURE – CONCEPTIONS AND INDICATORS - Joanna Wiśniewska (Acta Scientiarum Polonorum. Oeconomia, 2011)
The article presents different concepts of sustainable agriculture. It aims to define an economic sustainability of agriculture and to discuss the possible ways of its assessment. It states criteria of measurement and parameters used by the OECD and the European Commission (EC). The method of system analysis has been applied to study simultaneously different issues of sustainability, i.e. economic, environmental, social and institutional. The very last aspect has been considered because of the role of governmental intervention in the sector. The conclusion is that the opportunity of gaining permanent income parity is, beyond all question, an indicator of an economic and social sustainability of agriculture in the national economy.